Clinical characteristics, functional respiratory decline and follow-up in adult patients with primary ciliary dyskinesia. Issue 2 (5th July 2016) - Frija-Masson, Justine; Bassinet, Laurence; Honoré, Isabelle; Dufeu, Nadine; Housset, Bruno; Coste, André; Papon, Jean Francois; Escudier, Estelle; Burgel, Pierre-Régis; Maître, Bernard
Abstract : Introduction: Primary ciliary dyskinesia (PCD) is a genetic disease characterised by abnormalities in ciliary function, responsible for chronic pulmonary and sinonasal diseases. Adult clinical features and outcome are poorly described. Objectives: To assess the clinical characteristics and disease progression in adults with PCD. Methods: Bicentric retrospective study, focusing on adults (≥18 years) with an asserted diagnosis of PCD based on the presence of bronchiectasis with typical ultrastructural defect of cilia and/or situs inversus (SI). Clinical symptoms, respiratory function, extent of bronchiectasis, microbiology and molecular analysis were assessed. Results are expressed as median (25th; 75th centile). Results: 78 patients were included with a median follow-up of 8.1 years. 91% of patients had respiratory symptoms and 95% had chronic rhinosinusitis. Half of ultrastructural defects concerned dynein arms. Respiratory function was significantly lower in women (FEV1 =60% predicted (50; 76), vs 77% (62; 95), p=0.009) and in patients with chronic airway Pseudomonas aeruginosa (PA, n=21) infection (FEV1 =60% (48; 71) vs 75% (55; 89), p=0.04). FEV1 was associated with gender (regression coefficient for men =13.8, p=0.009), chest CT score (r=−0.42, p<0.001) but not with age at diagnosis, SI or body mass index. FEV1 decline was −13.4 mL/year (−42.8; +11.9) and was greater in women (−29.3 mL/year, (−59.7; −11.9), vs –2.0 mL/year (−26.9; +25.4), p=0.002). Three patients had severe respiratory failure. Conclusions: Alteration of respiratory function in adults with PCD is heterogeneous and usually moderate but appears more severe in women and in patients with chronic PA infection. Only 4% of patients develop chronic respiratory failure.